BUILDING VIRTUAL CAMPUS PLAN APPLICATION STMIK JAKARTA STI & K BY USING MACROMEDIA FLASH MX PROFESSIONAL 2004 - Aryo Budisatrio; Marzuki Marzuki, SKom, MMSI (Jurnal Sistem Informasi, 2005)
The development of computerized technology is increasingly prevalent at the timewith the internet on information technology. Through the internet facility is muchinformation can be found in various forms of both images and text. Through thistechnology STMIK Jakarta STI & K can provide more information about the facilityas well as other information. One of them is information on facilities available incampus buildings STMIK STI & K. Jakarta